Reform of Civil Justice in Ukraine: A Differentiation of Action Proceedings and Review of Court Decisions - Izarova, Iryna (Teisė, 2019)
[full article, abstract in English, abstract in Russian] During the reform of 2014–2017 Ukrainian legislation was approved significantly, among them the Constitution, laws, related to judiciary and litigation, enforcement as well. The advocacy reform is last. This has led to the evolutionary renewal of justice in Ukraine, which was positively faced by the international community. This article proposes to consider some components of civil justice reform, which were substantially updated, as well as to analyse their compliance with international and European standards. This refers to (1) a general review of judicial statistics and (2) new approaches to the trial of a court of first instance – order, simplified, general proceedings, criteria for demarcation of civil cases (3), and (4) peculiarities of settling a dispute with the participation of a judge. The conclusions summarize the most progressive results of reforms, as well as make suggestions on further development of the potential of civil justice.